BASES OF QUALITY MANAGEMENT OF GOODS BY AN ASSESSMENT OF LOYALTY OF THE CONSUMER - N. Zemlyanskaya; N. Kazakova; L. Mikhailova (Вестник университета, 2016)
In article it is shown that one of criteria of competitiveness of the organization is loyalty of end users, partners and her employees. Such fundamental categories as norm and mass of potrebitelny cost, a consumer assessment, quality and the range allow to reveal degree of satisfaction of the client. The way of an assessment of loyalty on the basis of definition of an index of consumer loyalty is considered, and also the algorithm of an assessment of this indicator is presented.